2021
DOI: 10.17583/rimcis.2020.6316
|View full text |Cite
|
Sign up to set email alerts
|

‘Sana All’ Inclusive Education amid COVID-19: Challenges, Strategies, and Prospects of Special Education Teachers

Abstract: People with Special Educational Needs and Disabilities (SEND) are confronted with diverse challenges as COVID-19 caused tremendous disruption in face-to-face educational settings. Apart from this situation, teachers are also facing difficulties in making their lessons adaptive and responsive to the educational learning needs of people with SEND. This article explores the challenges, strategies, and prospects of teachers for inclusive education during the pandemic. Using a qualitative approach, the researcher g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
0
20
0
8
Order By: Relevance
“…While the teachers in this study used exclusion strategies to compensate the lack of inclusivity in online teaching through additional one-to-one sessions, this exclusion and other strategies raise other issues such as social exclusion and poor communication skills (Hansen et al, 2020;Parmigiani et al, 2020) in the long run since the classes were conducted separately after school hours. Toquero (2021) argued that the opportunities for students to voice their learning are somewhat constrained in an online environment. Hence, ERT in the context of this study had indirectly marginalised students with additional learning needs, and supported digital exclusion to some extent.…”
Section: Inclusivity Of Ertmentioning
confidence: 99%
“…While the teachers in this study used exclusion strategies to compensate the lack of inclusivity in online teaching through additional one-to-one sessions, this exclusion and other strategies raise other issues such as social exclusion and poor communication skills (Hansen et al, 2020;Parmigiani et al, 2020) in the long run since the classes were conducted separately after school hours. Toquero (2021) argued that the opportunities for students to voice their learning are somewhat constrained in an online environment. Hence, ERT in the context of this study had indirectly marginalised students with additional learning needs, and supported digital exclusion to some extent.…”
Section: Inclusivity Of Ertmentioning
confidence: 99%
“…It was difficult for parents to attend all children's classes at the same time and manage it. The lack of gadgets caused barriers in online teaching and it affected the student's performance and their performance getting down day by day (Toquero, 2021). Internet connectivity issue and electricity issue is one of the main barriers which disturbed online sessions.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Special educational institutes made a plan to face and cope with the situation and started the provision of their services online and supported parents manage their children (Sakız, 2021). Parents, siblings, and other family members played an important role to implement the new set-up of online teaching for their children (Toquero, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hebebci, Bertiz, & Alan (2020) revealed that teachers highlight specific difficulties associated with online education, whereas Page, Charteris, Anderson, & Boyle (2021) find that students with special needs suffer academically and emotionally. Toquero (2021) found that teachers claim that special education students have comparable challenges during distance learning, but Sholikhati, Prayogo, & Santoso (2021), Asri, Cahyono, & Trisnani (2021), and Supratiwi, Yusuf, & Anggarani (2021) found that learners with special needs have difficulty with online learning. It is common knowledge that in accordance with the Personalized Education Plan designed for children who have special needs, children are expected to have instructional adaptations that call for one-on-one contact between students and instructors.…”
Section: Sometimes When My Child Won't Do Anything We Have To Force H...mentioning
confidence: 99%